Boric acid levels in fresh noodles and fish ball - Yiu, Pang Hung; Jian See,; Amarthalingam, Rajan; Bong, Choon Fah Joseph (Science Publications, 2008)
Boric acid (H3BO3) is detrimental to human health if consumed in excess. However, it continues to be used in the production of food especially noodles and some processed seafood such as fish ball. Five kinds of noodles and a type of fish ball were collected over a period of four weeks from a random sample of manufacturers in Bintulu, Sarawak, Malaysia. The boric acid in these food samples were analyzed by the curcumin-acetic acid method using 2-ethyl-1, 3-hexanediol (EHD) extraction. Results showed that yellow noodles contained highest concentration of boric acid throughout the four weeks with a mean of 2.034 μg g-1. In general, the mean concentrations in most food types were inconsistent throughout the sampling period and were relatively low compared to studies reported in Peninsular Malaysia. Although it is not a permitted food preservative or additive, this study showed that local food manufacturers were still using boric acid.